A novel H[alpha] control strategy for design of a robust dynamic routing algorithm in traffic networks - Abdollahi, F; Khorasani, K (IEEE journal on selected areas in communications, 2008)
The centralized routing problem is formulated as an Hinfin optimal control problem to achieve a robust routing performance in presence of multiple and unknown fast time-varying network delays.